Moral dilemmas in medieval thought from Gratian to Aquinas - Dougherty, M. V., 1973- (Cambridge University Press, 2011)
"The history of moral dilemma theory often ignores the medieval period, overlooking the sophisticated theorizing by several thinkers who debated the existence of moral dilemmas from 1150 to 1450. In this book Michael V. Dougherty offers a rich and fascinating overview of the debates which were pursued by medieval philosophers, theologians and canon lawyers, illustrating his discussion with a diverse range of examples of the moral dilemmas which they considered. He shows that much of what seems particular to twentieth-century moral theory was well-known long ago - especially the view of some medieval thinkers that some forms of wrongdoing are inescapable, and their emphasis on the principle 'choose the lesser of two evils'. His book will be valuable not only to advanced students and specialists of medieval thought, but also to those interested in the history of ethics."--